Precancerous lesion determinants in women attending cervical cancer screening at public health facilities in North Shoa Zone, Amhara, Ethiopia: an unmatched case-control study - Dereje Abebe Teklehaimanot; Abinet Dagnaw Mekuria; Abel Fekadu Dadi; Behailu Tariku Derseh (BMC, 2024)
Abstract Background Precancerous cervical lesions develop in the transformation zone of the cervix and progress through stages known as cervical intraepithelial neoplasia (CIN) 1, 2, and 3. If untreated, CIN2 or CIN3 can lead to cervical cancer. The determinants of cervical precancerous lesions are not well documented in Ethiopia. Therefore, this study aims to find the determinants of cervical precancerous lesions among women screened for cervical cancer at public health facilities. Methods A study conducted from January to April 2020 involved 216 women, consisting of 54 cases (positive for VIA during cervical cancer screening) and 162 controls (negative for VIA). It focused on women aged 30 to 49 undergoing cervical cancer screening. Multivariable logistic regression analysis assessed the link between precancerous lesions and different risk factors, considering a significance level of p < 0.05. Results Women who used oral contraceptives for a duration exceeding five years showed a nearly fivefold increase in the likelihood of developing precancerous lesions (Adjusted Odds Ratio (AOR) = 4.75; 95% CI: 1.48, 15.30). Additionally, early age at first sexual intercourse (below 15 years) elevated the odds of developing precancerous lesions fourfold (AOR = 3.77; 95% CI: 1.46, 9.69). Furthermore, women with HIV seropositive results and a prior history of sexually transmitted infections (STIs) had 3.4 times (AOR = 3.45; 95% CI: 1.29, 9.25) and 2.5 times (AOR = 2.58; 95% CI: 1.10, 6.09) higher odds of developing cervical precancerous lesions compared to their counterparts. Conclusion In conclusion, women who have used oral contraceptives for over five years, started sexual activity before the age of 15 and have a history of sexually transmitted infections, including HIV, are at higher risk of developing precancerous cervical lesions. Targeted intervention strategies aimed at promoting behavioural change to prevent early sexual activity and STIs are crucial for avoiding cervical precancerous lesions. It is crucial to introduce life-course principles for female adolescents early on, acknowledging the potential to prevent and control precancerous lesions at critical stages in life, from early adolescence to adulthood, encompassing all developmental phases.